„Stary, nieodpowiedni element”. Podoficerowie zawodowi sprzed 1939 roku w ludowym Wojsku Polskim w okresie czystek lat 1948–1949 - Kondracki, Tadeusz (1956– ) (Instytut Historii PAN, 2025)
The period between 1948 and 1949 was marked by intensified personnel purges in the “people’s” Polish Army. Officers whose military careers began during the Second Polish Republic were removed from the army for political reasons. A similar policy was pursued, where possible, in the professional non-commissioned officer corps. The longest-serving and most numerous pre-war members of the Professional Non-Commissioned Officers Corps remained in the administration, especially in the Navy, due to their expertise, which was dif-fi cult to replace. Plans to continue large-scale political purges had to be revised due to the expansion of the army after the outbreak of the Korean War (in June 1950).
p. 193-210
Summary in English.
Keywords: People’s Poland; professional non-commissioned offi cers; People’s Army; Personnel Department of the Ministry of National Defence; political purges; Poland. Polish Army (1944 -)